Dataset associated with 'Atmospheric radiative and oceanic biological productivity responses to increasing anthropogenic-combustion iron emission in the 1850-2010 period' - Rathod, Sagar (Colorado State University. Libraries, 2022)
Anthropogenic emission is an important component of the present-day iron cycle yet its long-term impacts on climate are poorly understood. Iron mineralogy strongly affects its radiative and oceanic interactions and was unrepresented in previous studies. We perform simulations using a mineralogy-based inventory and an atmospheric transport model and estimate the 1850–2010 global mean direct radiative forcing (DRF) to be +0.02 to +0.10 W/m2. We estimate that the CO2 sequestration of 0.2–13 ppmv over the last 150 years due to enhanced phytoplankton productivity by anthropogenic iron deposition causes an avoided CO2 forcing of −0.002 to −0.16 W/m2. While globally small, these impacts can be higher in specific regions; the anthropogenic DRF is +0.5 W/m2 over areas with more coal combustion and metal smelting, and anthropogenic soluble iron sustains >10% of marine net primary productivity in the high-latitude North Pacific Ocean, a region vulnerable to stratification due to climate change.
This dataset contains emission, deposition, and radiative fields to calculate Direct Radiative Forcing and Net Primary Productivity effects of anthropogenic iron emissions
Department of Atmospheric Science
Keywords: iron; anthropogenic; radiative forcing; biogeochemistry; emissions